Strengthening Indian environmental laws - "Sinha, G.N." (Dehradun, 2010)
Professional foresters are normally not well grounded in legal concepts and jurispnideritial aspects of law making on the environment, while lawyers don't ordinarily possess a sound understanding of the environmental issues and various ecosystem services emanating from (he environment. Strengthening Indian Environmental Laws -New Lessons and Approaches is a book which combines (he insights of a professional forester and a UK trained lawyer. This book argues for restructuring the Indian environmental law regime by drawing suitable lessons from the UK's and the European Union's environmental law regimes. This book is premised on the fact that similarities are greater within a given programmer across national boundaries than among different programmers within a country.
Keywords: Environmental law